Wakeup Call: Reviewing the Effects of Sleep on Decision-Making in Athletes and Implications for Sports Officials - Michele Lastella; Zozan Onay; Aaron T. Scanlan; Nathan Elsworthy; Nathan W. Pitchford; Grace E. Vincent (Montenegrin Sports Academy, 2020)
Although sports officials are essential in the adjudication of rules during competitions, research into officiating populations is preliminary. This review explores existing research on the effects of sleep loss on decision-making in athlete populations, to gain relevant insight into sports officials and the growing decision-making demands of their role. Specifically, cognitive factors that influence decision-making are identified, and the potential relationship between sleep/wake behaviours and decision-making in sports officials were examined. Particular focus was granted to sleep, specifically sleep restriction in athlete populations, and the hypothesized relationship between sleep/wake behaviours and decision-making in sports officials. Impaired sleep duration and quality has been shown to impair cognitive performance. In the context of sport, impairments to sleep can negatively impact motivation, physical strength, reaction time, and decision-making, all of which are imperative to the role of the sports official. Despite numerous studies demonstrating that sleep loss reduces cognitive performance in athletes, this review revealed that similar research in sports officials has surprisingly yet to be conducted. Since sports officials require a high level of cognitive and physical skills to make correct decisions, an inquiry into the influence of sleep on cognitive performance may encourage research that facilitates improved performance training methods for decision-making in officials. Such findings are important to maintain the standard of officiating and allow for the development of guidelines and strategies to manage sleep and optimize decision-making across various sporting codes.